Academic Preparation towards Improved World Class Maritime Shipboard Performance - Paraggua, Victoria; Magsino, Ronald; Diviva, Rachelle; Panado, Ana Lee M.; Millar, Jamila M. (JPAIR Multidisciplinary Research, 2017)
Continuous monitoring and evaluation are necessary in keeping graduates abreast of the trends and demands in maritime in order not to lag behind in a highly competitive environment like the shipping industry. The study evaluated the academic preparation and shipboard training performance of the PMMA cadets as basis for improvement of the program towards customer satisfaction. The descriptive design was utilized to gather and evaluate the perception of the respondents. The trainee-respondents rated the curriculum, faculty competency, and laboratory and equipment as very satisfactory. Evaluator-respondents rated the work competency, ethical standards, and knowledge and skills of the trainees as very satisfactory. Trainees positively regarded the preparation of reports. They also handled tasks and functions stipulated in their training record book though there are some areas where a significant majority did not experience. The latest trends and demands that should be addressed and incorporated in the maritime curriculum are the following: full compliance with security and safety; installation and use of up-to-date and modern navigational equipment; the presence of electronically controlled camless main engine; simpler but durable cargo handling equipment; and garbage management system. The weaknesses and gap revealed that the maritime curriculum and shipboard training need consideration and reflection to maintain the country’s status as the prime provider and producer of highly qualified marine officers.